ANALYSIS OF NURSING CARE PLAN FOR PULMONARY TUBERCULOSIS PATIENTS WITH PURSED LIPS BREATHING INTERVENTION AT HOSPITAL WEST JAVA PROVINCE - Riesma Pratiwi Nuril Azmi; Vivop Marti Lengga (Department of Nursing, Faculty of Medicine, Universitas Sriwijaya, 2025)
Pulmonary tuberculosis remains a global health problem, with Indonesia ranking second in the world in terms of TB cases, with West Java recording high cases. Although pharmacological therapy is the mainstay of pulmonary tuberculosis management, non-pharmacological interventions such as pursed lips breathing (PLB) have been shown to improve ventilation, reduce CO₂ retention, and increase oxygen saturation, however, its application in nursing practice is still very limited. This study aims to analyze the application of pursed lips breathing in pulmonary TB patients at Hospital in West Java Province. This study uses a case study approach with the nursing problem of ineffective breathing patterns and the administration of pursed lips breathing in the Umar bin Khattab 3 room. Based on the results of a physical examination obtained by the patient, the respiratory rate was 27 breaths/minute, oxygen saturation was 93%, accessory muscles were used for breathing, there was rales in the left lung, and thick sputum was difficult to expel. Based on the assessment results, three nursing diagnoses were established: ineffective airway clearance related to airway hypersecretion, ineffective breathing pattern related to breathing effort obstruction, and sleep pattern disturbance related to lack of sleep control. Interventions included airway management, effective coughing exercises, sleep support, nebulization, oxygen therapy, and pursed-lip breathing exercises during the three days of treatment. The evaluation results showed significant improvement with oxygen saturation increasing to 97%, respiratory rate decreasing to 20 breaths/minute, reduced sputum, and improved sleep quality. These findings confirm that pursed-lips breathing is an effective non-pharmacological intervention that supports pharmacological therapy in improving respiratory function and quality of life in pulmonary TB patients. Therefore, a holistic nursing approach is recommended for optimal TB care.